DMC1 mutation that causes human non-obstructive azoospermia and premature ovarian insufficiency identified by whole-exome sequencing. Issue 3 (13th January 2018) - He, Wen-Bin; Tu, Chao-Feng; Liu, Qiang; Meng, Lan-Lan; Yuan, Shi-Min; Luo, Ai-Xiang; He, Fu-Sheng; Shen, Juan; Li, Wen; Du, Juan; Zhong, Chang-Gao; Lu, Guang-Xiu; et al.
Abstract : Background: The genetic causes of the majority of male and female infertility caused by human non-obstructive azoospermia (NOA) and premature ovarian insufficiency (POI) with meiotic arrest are unknown. Objective: To identify the genetic cause of NOA and POI in two affected members from a consanguineous Chinese family. Methods: We performed whole-exome sequencing of DNA from both affected patients. The identified candidate causative gene was further verified by Sanger sequencing for pedigree analysis in this family. In silico analysis was performed to functionally characterise the mutation, and histological analysis was performed using the biopsied testicle sample from the male patient with NOA. Results: We identified a novel homozygous missense mutation (NM_007068.3: c.106G>A, p.Asp36Asn) in DMC1, which cosegregated with NOA and POI phenotypes in this family. The identified missense mutation resulted in the substitution of a conserved aspartic residue with asparaginate in the modified H3TH motif of DMC1. This substitution results in protein misfolding. Histological analysis demonstrated a lack of spermatozoa in the male patient's seminiferous tubules. Immunohistochemistry using a testis biopsy sample from the male patient showed that spermatogenesis was blocked at the zygotene stage during meiotic prophase I. Conclusions: To the best of our knowledge, this is the first report identifying DMC1 as the causative gene for human NOA and POI. Furthermore, our pedigree analysis shows an autosomal recessive mode of inheritance for NOA and POI caused by DMC1 in this family.